The Use of Natural Environment Media in Early Childhood Learning at RA Alkhairat Kalumpang - Wahyuni Abubakar; H. Haryati; Nursin Sapil; Santi M.J Wahid (Golden Ratio of Social Science and Education, 2026)
This study aimed to examine the use of natural resources in early childhood learning at RA Alkhairat Kalumpang. The study used a descriptive qualitative approach with three teachers and 42 students from Groups A and B as subjects. Data were collected through observations, interviews, and documentation and analyzed using data reduction, data presentation, and conclusion drawing techniques. The results showed that teachers utilized various natural resources, such as leaves, gravel, soil, sand, and water, in learning activities, although they were not systematically planned in written learning materials. The use of natural resources can create active, contextual, and child-centered learning. Children show higher levels of participation and enthusiasm, as well as positive development in cognitive, motor, socio-emotional, and language aspects. These findings are in line with Piaget's cognitive development theory, the Montessori approach, and contextual learning, which emphasize the importance of concrete learning experiences and direct interaction with the environment. The obstacles encountered included limited lesson planning, preparation time, and concerns about the cleanliness and safety of natural resources. This study concludes that natural resources are effective, economical, and relevant learning resources for improving the quality of early childhood learning.